Study on the Damage Evolution Process and Fractal of Quartz-Filled Shale under Thermal-Mechanical Coupling. (7th January 2021) - Wu, Zhonghu; Song, Huailei; Li, Liping; Zhou, Zongqing; Zuo, Yujun; Sun, Wenjibin; Liu, Hao; Lou, Yili
Abstract : Filling of brittle minerals such as quartz is one of the main factors affecting the initiation and propagation of reservoir fractures in shale fracturing, in order to explore the failure mode and thermal damage characteristics of quartz-filled shale under thermal-mechanical coupling. Combining the theory of damage mechanics and thermoelasticity, RFPA 2D -Thermal is used to establish a numerical model that can reflect the damage evolution of shale under thermal-solid coupling, and the compression test under thermal-mechanical coupling is performed. The test results show that during the temperature loading process, there is a temperature critical value between 60°C and 75°C. When the temperature is less than the critical temperature, the test piece unit does not appear obvious damage. When the temperature is greater than the critical temperature, the specimen unit will experience obvious thermal damage, and the higher the temperature, the more serious the cracking. Under the thermal-mechanical coupling of shale, the tensile strength and elastic modulus of shale show a decreasing trend with the increase of temperature. The failure modes of shale under thermal-solid coupling can be roughly divided into three categories: "V"-shaped failure (30°C, 45°C, and 75°C), "M"-shaped failure (60°C), and inverted " λ "-shaped failure (90°C). The larger the fractal dimension, the more complex the failure mode of the specimen. The maximum fractal dimension is 1.262 when the temperature is 60°C, and the corresponding failure mode is the most complex "M" shape. The fractal dimension is between 1.071 and 1.189, and the corresponding failure mode is "V" shape. The fractal dimension is 1.231, and the corresponding failure mode is inverted " λ " shape.